Keuangan Syariah Dalam Literasi Modern - Dewanata, Pandu; Anwar US, Kasful (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2021)
This article contains an explanation of the management of Islamic finance in modern literacy in Indonesia, nowadays it is understood that Indonesia still has a literacy level which is considered quite low, so it needs to be reviewed. This journal only describes descriptively about the material and theories regarding financial literacy and financial management in a person which is an important science to be able to improve his financial well-being.